The solution of the system of equation is the intersection point of the two quadratic equations, so we need to equate both equations, that is,
![2x^2-3x-10=-3x^2+20](https://tex.z-dn.net/?f=2x%5E2-3x-10%3D-3x%5E2%2B20)
So, by moving the term -3x^3+20 to the left hand side, we have
![5x^2-3x-30=0](https://tex.z-dn.net/?f=5x%5E2-3x-30%3D0)
Then, in order to solve this equation, we can apply the quadratic formula
![x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
In our case, a=5, b=-3 and c=-30. So we get
![x=\frac{3\pm\sqrt{(-3)^2-4(5)(-30)}}{2(5)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B3%5Cpm%5Csqrt%7B%28-3%29%5E2-4%285%29%28-30%29%7D%7D%7B2%285%29%7D)
which gives
![\begin{gathered} x=2.76779 \\ and \\ x=-2.16779 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%3D2.76779%20%5C%5C%20and%20%5C%5C%20x%3D-2.16779%20%5Cend%7Bgathered%7D)
By substituting these points into one of the functions, we have
![f(2.76779)=-2.982](https://tex.z-dn.net/?f=f%282.76779%29%3D-2.982)
and
![f(-2.16779)=5.902](https://tex.z-dn.net/?f=f%28-2.16779%29%3D5.902)
Then, by rounding these numbers to the nearest tenth, we have the following points:
![\begin{gathered} (2.8,-3.0) \\ and \\ (-2.2,5.9) \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%282.8%2C-3.0%29%20%5C%5C%20and%20%5C%5C%20%28-2.2%2C5.9%29%20%5Cend%7Bgathered%7D)
Therefore, the answer is the last option